Curcumin Protects against UVB-Induced Skin Cancers in SKH-1 Hairless Mouse: Analysis of Early Molecular Markers in Carcinogenesis. (19th July 2012) - Tsai, Kuen-Daw; Lin, Jung-Chung; Yang, Shu-mei; Tseng, Min-Jen; Hsu, Jeng-Dong; Lee, Yi-Ju; Cherng, Jaw-Ming
Abstract : Curcumin (CUR) has been shown to possess a preventive effect against various cancers and interfere with multiple-cell signaling pathways. We evaluated the protective effects of CUR in regression of UVB-induced skin tumor formation in SKH-1 hairless mice and its underlying early molecular biomarkers associated with carcinogenesis. Mice irradiated with UVB at 180 mJ/cm 2 twice per week elicited 100% tumor incidence at 20 weeks. Topical application of CUR prior to UVB irradiation caused delay in tumor appearance, multiplicity, and size. Topical application of CUR prior to and immediately after a single UVB irradiation (180 mJ/cm 2 ) resulted in a significant decrease in UVB-induced thymine dimer-positive cells, expression of proliferative cell nuclear antigen (PCNA), terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling, and apoptotic sunburn cells together with an increase in p53 and p21/Cip1-positive cell population in epidermis. Simultaneously, CUR also significantly inhibited NF- κ B, cyclooxygenase-2 (COX-2), prostaglandin E2 (PGE2), and nitric oxide (NO) levels. The results suggest that the protective effect of CUR against photocarcinogenesis is accompanied by downregulation of cell proliferative controls, involving thymine dimer, PCNA, apoptosis, transcription factors NF- κ B, and of inflammatory responses involving COX-2, PGE2, and NO, while upregulation of p53 and p21/Cip1 to prevent DNA damage and facilitate DNA repair.